Increased electromechanical sensitivity of polysiloxane elastomers by chemical modification with thioacetic groups. (15th January 2020) - Perju, Elena; Ko, Yee Song; Dünki, Simon J.; Opris, Dorina M.
Abstract: Chemically cross-linked polydimethylsiloxane (PDMS) elastomers have gained importance as a dielectric in elastic capacitor actuators, which elongate when electrically charged. Common PDMS elastomers have a dielectric permittivity of only about 3 and thus elongations interesting for real applications occur only at high voltages. In this work, a new class of silicone-based elastomers with increased permittivity are synthesized starting from polymethylvinylsiloxane and thioacetic acid via a photo-induced thiol-ene reaction, whereby polar thioacetate groups are introduced at every siloxy unit. The silanol end-groups of the formed polymer are subsequently used for cross-linking into thin films using a condensation reaction with poly(methylhydrosiloxane- co -dimethylsiloxane). These films show good mechanical properties and have a low glass transition temperature (-58 °C), which allows for a wide range of use temperatures. Further they have an increased permittivity ( ε'  = 4.7) and an increased sensitivity to electric field as compared to regular polydimethylsiloxane elastomers. Our new elastomers are easily accessible and can be processed into very thin films, which allows access to actuators operable way below 1000 V. An actuation strain of 12.8% at an electric field of 21.5 V/μm was measured. Graphical abstract: Image 1 Highlights: Novel silicone-based elastomers modified with thioacetic groups were prepared. Surface treated silica particles improve the mechanical properties of the formed elastomers. The increased permittivity and the optimized elasticity allowed construction of DEA responsive to a low electric field. The elastomers can be processed in thin films from which actuators operated at low voltages were constructed.